The industrialisation of Soviet Russia : 2. the Soviet collective farm, 1929-1930 - Davies, R.W. (London : Macmillan Press, 1989)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: planeconomie; Sovjet-Unie.